High‐Quality Yeast‐2‐Hybrid Interaction Network Mapping. Issue 3 (26th June 2018) - Altmann, Melina; Altmann, Stefan; Falter, Claudia; Falter‐Braun, Pascal
Abstract: In this article, we describe a Y2H interaction mapping protocol for systematically screening medium‐to‐large collections of open reading frames (ORFs) against each other. The protocol is well suited for analysis of focused networks, for modules of interest, assembling genome‐scale interactome maps, and investigating host‐microbe interactions. The four‐step high‐throughput protocol has a demonstrated low false‐discovery rate that is essential for producing meaningful network maps. Following the assembly of yeast expression clones from an existing ORFeome collection, we describe in detail the four‐step procedure that begins with the primary screen using minipools, followed by secondary verification of primary positives, identification of candidate interaction pairs by sequencing, and a final verification step using fresh inoculants. In addition to this core protocol, aspects of network mapping and quality control will be discussed briefly. © 2018 by John Wiley & Sons, Inc.